2023
DOI: 10.3390/ijms242317074
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Receptors and Metabolic Enzymes in Hen Reproductive Tissues

Anna Hrabia,
Kinga Kamińska,
Magdalena Socha
et al.

Abstract: In recent years, vitamin D3 has been revealed as an important regulator of reproductive processes in humans and livestock; however, its role in the female reproductive system of poultry is poorly known. The aim of this study was to examine vitamin D3 receptor (VDR and PDIA3) and metabolic enzyme (1α-hydroxylase and 24-hydroxylase) mRNA transcript and protein abundances, and protein localization within the hen ovary, oviductal shell gland, pituitary, liver, and kidney. We demonstrated, for the first time, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A recent meta-analysis has shown that VD supplementation to PCOS women could decrease the occurrence rates of early miscarriage and premature delivery [ 53 ]. The nuclear receptor of VD (VDR) and 1,25(OH)2D3 membrane binding protein are expressed in both ovarian granulosa and theca cells [ 61 , 62 ]. It has been found that VD can regulate the expression of enzymes in the VDR and ovary, ultimately regulating ovarian function [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis has shown that VD supplementation to PCOS women could decrease the occurrence rates of early miscarriage and premature delivery [ 53 ]. The nuclear receptor of VD (VDR) and 1,25(OH)2D3 membrane binding protein are expressed in both ovarian granulosa and theca cells [ 61 , 62 ]. It has been found that VD can regulate the expression of enzymes in the VDR and ovary, ultimately regulating ovarian function [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, in addition to Meg and CUB, 1α-hydroxylase is expressed in vitamin D target tissues, such as osteoblasts and the placenta, and the 25(OH)D 3 -DBP complex is taken up to produce 1,25(OH) 2 D 3 , indicating that 1,25(OH) 2 D 3 regulates target tissues via an autocrine or paracrine pathway independent of circulating 1,25(OH) 2 D 3 of kidney origin [28,29]. In laying hens, it has been demonstrated that vitamin D metabolizing enzymes, such as 1α-hydroxylase and 24-hydroxylase, are present in the eggshell gland and intestinal tract, in addition to the kidney [10,30]. Consequently, uptake of the 25(OH)D 3 -DBP complex by Meg and CUB in the intestinal tract, oviduct, and medullary bone of laying hens may regulate calcium metabolism via local vitamin D metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D 3 is synthesized in the skin from 7-dehydrocholesterol by ultraviolet irradiation in sunlight or is supplemented directly from dietary sources [7]. Vitamin D 3 is transported to the liver and converted to 25-hydroxy vitamin D 3 (25(OH)D 3 ) by 25-hydroxylase (Cyp27A1), which then binds to vitamin D-binding protein (DBP), circulates in the blood, is taken up by the kidneys, and is converted to 1,25(OH) 2 D 3 by 25(OH)D 3 -1α hydroxylase (Cyp27C1 in birds, Cyp27B1 in mammals) [8][9][10]. 1,25(OH) 2 D 3 is biologically active and binds to vitamin D receptors to promote intestinal absorption and renal reabsorption of calcium, as well as the formation of medullary bone to maintain circulating calcium levels in the blood and promote eggshell formation in the oviduct [11,12].…”
Section: Introductionmentioning
confidence: 99%